Optimization of operating conditions for supercritical fluid extraction of patchouli (Pogostemon cablin) essential oil. - Tan, Teng Ju; Nordin, Mohd Shukor; Haron, Normah (2019)
Patchouli (Pogostemon cablin) is a widely valued plant for its aromatic and medicinal properties. As an industrial important aromatic plant, the method used to extract the patchouli essential oil should be innovated. Supercritical fluid extraction (SFE) is a method that capable of selectively extract the desirable compounds of essential oil at high yield by manipulation of SFE conditions. Thus, this study aims to determine the effect of temperature and pressure of SFE on the yield and quality of patchouli essential oil. The patchouli leaves were subjected to SFE under different conditions of temperature (35 and 55oC) and pressure (10, 35 and 60 MPa). The yield of the SFE was determined by total oil content (TOC) and the chemical composition of the extracted oil was analysed by gas chromatography-mass spectrometry (GC-MS) and compared with chemical profile of commercial patchouli essential oil produced by steam distillation. The TOC analysis showed that the highest yield was obtained under the pressure of 60 MPa at 55°C, with 3.0586 ± 0.23 % TOC and the lowest yield was observed under the pressure of 10 MPa at 55°C, with only 0.5648 ± 0.19 % TOC. The effects of pressure and temperature on the extraction yield (TOC) were statistically significant. In GC-MS analysis, thirteen compounds were identified in the steam-distilled oil, while the highest number of compounds observed in SFE’s were only eleven. Despite of this, the oils extracted with scCO2 had higher quality compared to the steam-distilled oil, based on the quantity of two important compounds (patchoulol and α-patchoulene) that specifically determined the quality of the patchouli oil. SFE at 10 MPa; 35oC gave the highest composition of patchoulol (73.65 ± 3.60 %), while SFE at 60 MPa; 55oC resulted in highest amount of α-patchoulene (5.01 ± 0.20 %). Steam distillation’s oil was found to acquire the least amount of patchoulol among all (38.95 %), but contained fairly high concentration of α-patchoulene (3.86 %). The optimum SFE conditions for patchouli essential oil were 60 MPa; 55oC, which gave the highest oil yield with 59.30 ± 6.16 % of total percentage of both patchoulol and α-patchoulene. Overall, the study has demonstrated that the oil from SFE had better quality than the oil from steam distillation.